La Cour provinciale et l'art. 96 de l'A.A.N.B. - Deslauriers, Jacques (Les Cahiers de droit, 1977)
In the Province of Quebec, the Provincial Court constitutes one of the most important benches after the Court of Appeal and the Superior Court. At its beginning in 1869, the Provincial Court was termed the Magistrate's Court and its juridiction was very circumscribed. The constitutional problem arising from the existence of such a court was not obvious as it is today.